Traditions of Savardan biy (Mongolian Journal of Arts and Culture, 2025)
Savardan biy is a folk art heritage that has been passed down among the Oirad Mongols since ancient times, and is an important branch of dance performance, and one of the representative intangible heritages of the Oirad Mongols of China. Based on the theory and methodology of ethnic dance, this article attempts to integrate savardan with its culture, history, and society. Savardan is not only a dance movement, but also a comprehensive expression of the Mongolians› respectful customs and upbringing traditions. At the beginning of the dance, the rules such as bowing down three times and passing the dance on the knees and the floor, taking into account the age difference, regulated social relations and had educational significance. In addition, the punishment rituals such as “yandlakh”, “argamz alruthu”, and “star show”encouraged everyone to learn to dance and had an important impact on preserving the heritage. Therefore, savardan biy is not only an expression of festive art, but also an important tool for daily life, culture, and education. It is of particular importance to comprehensively study, document, and pass it on in its entirety to strengthen cultural immunity.Савардан бийгийн ёс уламжлалХураангуй: Савардан бий нь ойрад монголчуудын дунд эрт үеэс уламжлагдан ирсэн ардын язгуур урлагийн өв бөгөөд бий биелгээний нэгэн чухал салбар, БНХАУ-ын ойрад монголчуудын төлөөлөхүйц биет бус өвийн нэг юм. Тус өгүүлэл нь угсаатны бүжгийг судлах онол арга зүйд тулгуурлан, савардан бийгийн түүх, соёл, нийгэмтэй нь хамтруулан судлах оролдлого хийсэн болно. Савардан зөвхөн бүжгийн хөдөлгөөн бус, харин монголчуудын хүндэтгэлийн ёс заншил, хүмүүжлийн уламжлалыг цогцоор нь илэрхийлдэг. Бийгийн эхэнд гурвантаа сөгдөн мөргөх, насны ялгааг харгалзан өвдөг болон даланд гар хүрч бийг дамжуулах зэрэг дэг ёс нь нийгмийн харилцааг зохицуулах, мөн хүмүүжлийн ач холбогдолтой байжээ. Мөн “яндлах”, “аргамж алдруулах”, “од үзүүлэх” зэрэг торгуулийн зан үйл нь хүн бүрийг бийлж сурахад урамшуулж, өв уламжлалыг бататган үлдээхэд чухал нөлөө үзүүлсэн байна. Иймд савардан бий нь баяр ёслолын урлагийн илэрхийлэл төдий бус, өдөр тутмын амьдрал, ахуй соёл, хүмүүжлийн чухал хэрэгсэл бөгөөд түүнийг цогцоор нь судлан баримтжуулж, бүрэн бүтнээр нь өвлүүлэх нь соёлын дархлааг бэхжүүлэхэд онцгой ач холбогдолтой юм.Түлхүүр үгс: Жангар тууль, товшуурын аяс, хүндэтгэлийн ёс, торгуулийн арга